(untitled) (Canadian Medical Education Journal, 2022)
COVID-19 restrictions have prompted many medical schools to shift to virtual interview methods for medical school applicant selection. While extensive reflection has been documented around both the process and benefits of transitioning to a virtual Multiple Mini Interview (V-MMI) format, less attention has been given to examining the unintended consequences of this adaptation on increasing representation from underrepresented groups. In this Black Ice article, we consider the equity implications of taking a virtual approach to conducting MMIs and present some practical tips to ensure medical schools are giving attention to and addressing equity issues that may affect applicant and assessor engagement and success. The following seven recommendations include actionable steps medical schools can take immediately to optimize the interview process. This guide can be adapted to residency matching services and other health professions education programs that utilize the MMI.